What do we know and what should we do about AI? - Luger, Ewa (London : SAGE Publications Ltd, 2023)
The idea of Artificial Intelligence (AI) has taken the world by storm. From fears over killer robots in sci-fi dystopias, to driverless cars in real life, we are both inspired and horrified by the prospect of an advanced intelligence that is not our own. Could AI take over the world? Will it take all of our jobs? Has Google really created a sentient chatbot, and is AI racing towards human intelligence, or is it just horribly misunderstood? These common questions point us towards an unknown and troubling future. What we do know is that we are in the midst of a hype cycle, with huge amounts of funding and focus galvanising progress. Whether AI truly lives up to this hype remains to be seen, but this once niche idea has suddenly evolved into a global multibillion dollar industry. In this short and accessible book, Ewa Luger explains what we mean when we talk about AI, explores how we got here, describes what we are doing about it, where the field is heading, and where we should go next. ABOUT THE SERIES: The 'What Do We Know and What Should We Do About...?' series offers readers short, up-to-date overviews of key issues often misrepresented, simplified or misunderstood in modern society and the media. Each book is written by a leading social scientist with an established reputation in the relevant subject area. The Series Editor is Professor Chris Grey, Royal Holloway, University of London.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Artificial intelligence; Artificial intelligence -- Social aspects